Directions of Expenditure of Extrabudgetary Funds in Budgetary Organizations (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article examines the peculiarities of the use of extra-budgetary funds in budgetary organizations of Uzbekistan. The article describes the main directions of spending these funds, such as remuneration and bonuses for employees, the purchase of equipment and materials, repair and construction work, the organization of events, as well as social programs and charity extrabudgetary funds. In conclusion, recommendations are offered to improve the efficiency of their use.